MARINE ECOTOURISM DEVELOPMENT STUDIES SITIRIS-leak BEACH CENTRAL DISTRICT OF NORTH SUMATRA PROVINCE TAPANULI - Algino Panuntun Akbar; Dessy Yoswaty; Joko Samiaji (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTThis research was conducted in November 2019 in Sitiris-tiris Coast of Central Tapanuli, North Sumatra. This study aims to determine the potential for marine ecotourism in Province and development strategy. The method used in this study was a survey method to collect qualitative and quantitative data such as interviews, questionnaires and measurement data at the study site. The research location has 3 stations, the first station was in place adjacent to Coral Island, station 2 was located close to tourist attractions and the station 3 located in coastal areas adjacent to the pier. The environmental parameters measured were temperature, brightness, salinity, pH and current velocity.Sitiris-tiris Coast had potential and a tremendous prospect to be developed as an area of marine ecotourism. The natural beauty of the pristine and natural beach make great chance to make Sitiris-tiris Coast as marine ecotourism region. Suitability index based travel, suitability value for tourism activities Sitiris-tiris Coast included in the category of very suitable (S1), with values ranging between 78.57-90.47% and the average value of 84.52%. The value was supporting to undertake the development of ecotourism in Sitiris-tiris Coast. Keywords: Sitiris-tiris Beach, Development, Marine Ecotourism